Do oxidized low-density lipoproteins link to extra hepatic manifestations in chronic, non-cirrhotic HCV patients? - Dina Johar; Ahmed Hamed Bedair El-Assal; Mahmoud Mohamed Abou-El-Makarem; Essam Foad A. Hammouda; Mohamed Soliman Hegazy; Samy Zaky (Metabolism Open)
Background: Tissue damage by viral hepatitis is a major cause of morbidity and mortality worldwide. Oxidation reactions and reactive oxygen species (ROS) transform proteins and lipids in plasma low-density lipoproteins (LDL) into the abnormal oxidized LDL (ox-LDL). Hepatitis C virus (HCV) infection induces oxidative/nitrosative stress from multiple sources, including the inducible nitric oxide synthase (iNOS), the mitochondrial electron transport chain, hepatocyte NAD(P)H oxidases (NOX enzymes), and inflammation. Further, HCV decreases reduced glutathione (GSH) synthesis and regeneration. Design: Cross-section. Objective: to quantify ox-LDL in serum of chronic non-cirrhotic HCV patients, and to assess ox-LDL association with HCV-induced extra hepatic manifestations. Patients and methods: Twenty chronic, non-cirrhotic HCV female patients with extra hepatic manifestations, twenty chronic, non-cirrhotic female HCV patients without extra hepatic manifestations and twenty healthy age, sex matched controls. Methods: Serum was used for determination of liver function tests, ox-LDL and the extracellular antioxidant enzyme Superoxide Dismutase EC CuZn-SOD. Results: Patients with extra hepatic manifestations had statistically higher ox-LDL (76.63 ± 6.86 μg/L) than patients without extra hepatic manifestations (63.05 ± 6.6 μg/L) p < 0.001, and both patient groups had higher ox-LDL levels than the control group (44.1 ± 4.1 μg/L) p < 0.001. EC CuZn-SOD correlated negatively with ox-LDL in HCV patients with extra hepatic manifestation only. Conclusion: Extra hepatic manifestations were not risk for anthropometric changes seen with HCV infection. Extra hepatic manifestations were associated with high serum ox-LDL. High serum levels of ox-LDL associated with- or were due to deregulated expression of serum EC CuZn-SOD in chronic HCV patients.